2001
DOI: 10.2143/ac.56.2.2005623
|View full text |Cite
|
Sign up to set email alerts
|

Associated vascular lesions in patients undergoing coronary artery bypass grafting

Abstract: Atherosclerotic involvement of extracoronary arteries in patients undergoing myocardial revascularization can cause severe postoperative complications and increase postoperative mortality. Between January and November 1998, routine preoperative echo-Doppler study of carotid vessels, abdominal aorta and iliac-femoral arteries was performed in all patients undergoing coronary artery bypass grafting (CABG) at our institution, in order to assess the prevalence and the degree of associated vascular lesions. Correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…3,[5][6][7]19 Moreover, any causal correlation between carotid hemodynamics and cerebrovascular pathology could be confounded by similar worsening hemodynamics in the cardiac, vertebrobasilar, or cerebral arteries. 20 In this study PWML, but not DWML, were associated with WSS. Interestingly, previous investigators have found a similar distinction as PWML, but not DWML, were associated with total cerebral blood flow, intima-media thickness, plaques in the carotid artery, and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 40%
“…3,[5][6][7]19 Moreover, any causal correlation between carotid hemodynamics and cerebrovascular pathology could be confounded by similar worsening hemodynamics in the cardiac, vertebrobasilar, or cerebral arteries. 20 In this study PWML, but not DWML, were associated with WSS. Interestingly, previous investigators have found a similar distinction as PWML, but not DWML, were associated with total cerebral blood flow, intima-media thickness, plaques in the carotid artery, and atrial fibrillation.…”
Section: Discussionmentioning
confidence: 40%
“…Yapılan araştırmalar Amerika'da her yıl 300.000'den fazla hastaya KABG uygulandığını gös-termektedir. [20] Koroner arter bypass greftleme ameliyatının ameliyat sonrası birçok komplikasyonu bulunmaktadır ve bunlar içerisinde inme, ameliyat sonrası nörolojik komplikasyonların başında gelen ve en korkulanıdır. İnmeyi önlemeye yönelik birçok çalışma yapılmış olmasına rağmen, KABG sonrası inme halen en önemli mortalite ve morbidite nedenlerinin başında gelmekte ve hastanede kalış süresini, hastane maliyetini artırmakta, hastanın yaşam kalitesini ise azaltmaktadır.…”
Section: Discussionunclassified
“…There is a general agreement that coronary artery disease represents only a part of a more widespread atherosclerotic disease, and a clear correlation has been found between extent of coronary artery disease and incidence of carotid and peripheral vascular disease [6,15]. The degree of arterial involvement varies according to age, sex, geographic location and risk factors of the population [16].…”
Section: Discussionmentioning
confidence: 99%
“…D'Agostino et al [18] found in their patients undergoing CABG an incidence of carotid stenosis greater than 50% in 20% of patients, and greater than 80% in 8%. Our previous report showed that 61.6% of patients undergoing CABG have some carotid stenosis, meanwhile 10.2% have a hemodinamically significant carotid stenosis, exposing the patient to the risk of perioperative neurological injury [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation